An in Vitro and in Silico Study of Antioxidant Properties of Curcuminoid N-Alkylpyridinium Salts: Initial Assessment of Their Antitumoral Properties - Echeverria-Morgado, J (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
In this work, we report the synthesis of curcuminoids with ionic liquid characteristics, obtained by incorporating alkyl-substituted pyridinium moiety rather than one phenyl group through a two-step process. The antioxidant capacity of the obtained compounds was evaluated in vitro by 1,1-diphenyl-picrylhydrazyl (DPPH) free radical scavenging and ferric reducing antioxidant power (FRAP) assays, showing that some derivatives are more potent than curcumin. Pyridine curcuminoids (group 4) and curcuminoid N-alkylpyridinium salts with two methoxyl groups in the phenyl ring (group 7), presented the best antioxidant capacity. The experimental results were rationalized by density functional theory (DFT) calculations of the bond dissociation enthalpy (BDE) for O-H in each compound. The computational calculations allowed for insight into the structural-antioxidant properties relationship in these series of compounds. BDEs, obtained in the gas phase and water, showed a notable impact of water solvation on the stabilization of some radicals. The lower values of BDEs in the water solution correspond to the structurally related compounds cur-cuminoid-pyridine 4c and curcuminoid pyridinium salt 7a, which is consistent with the experimental results. Additionally, an assessment of cell viability and cell migration assays was performed for human colon cancer (HT29), human breast cancer (MCF7) cells, in addition to NIH3T3 murine fibroblast, as a model of non-cancer cell type. These compounds mainly cause inhibition of the cell migration observed in MCF7 cancer cells without affecting the non-tumoral NIH3T3 cell line: Neither in viability nor in migration. © 2022 by the authors. Licensee MDPI, Basel, Switzerland.
Keywords: pyridinium salts; curcuminoids; antioxidants; Pabon reaction; cancer